Impact of patient characteristics on edentulous subjects' preferences for prosthodontic rehabilitation with implants. Issue 3 (25th February 2019) - Leles, Cláudio R.; Dias, Danilo R.; Nogueira, Túlio E.; McKenna, Gerald; Schimmel, Martin; Jordão, Lidia M. R.
Abstract: Objective: The aim of this study was to assess the influence of patient characteristics on edentulous subjects' preferences for different prosthodontic treatments with implants. Materials and methods: A cross‐sectional study was carried out with 131 edentulous subjects referred for treatment at a university clinic. Participants received detailed information about available treatment options and were asked to rank their preferences among three alternatives for rehabilitation of the maxilla and mandible: conventional dentures (CD), 2‐implant‐retained overdentures (IOD), or 4‐implant fixed dentures (IFD). Individual data and prosthodontic‐related variables were assessed through interviews. Oral health‐related quality of life impacts was measured using the Brazilian version of the Oral Health Impact Profile for edentulous subjects (OHIP‐Edent). Descriptive statistics, bivariate tests, and binary and multinomial logistic regressions were used for data analysis. Results: The majority of participants chose CD as their most preferred treatment for the maxilla (45.8%), while IFD was the most prevalent choice for the mandible (38.9%). Regression analysis showed that the OHIP‐Edent "oral pain and dysfunction" (OPD) domain scores were positively associated with IOD preference for the maxilla (OR = 1.31; p  = 0.010) and mandible (OR = 1.46; p  = 0.002) and with IFD preference for the mandible (OR = 1.20; p  = 0.031). Subjects with lower levels of formal education and those with lower income levels were less likely to choose IFD. Conclusion: Level of education, income, and perceived quality of life impacts are potentially predictive variables of edentulous patients' preference for rehabilitation with implants. These factors may constitute important aspects to be considered by clinicians when treatment planning for edentulous patients.